(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Traffic control and enforcement of various traffic and parking regulations form an important part of the Traffic Enforcer’s function in the safe movement of pedestrians, vehicles, and bicycles on the road. To allow for the safe movement of traffic, the enforcers take appropriate enforcement action to help keep the community in compliance with appropriate traffic laws. Like other countries, the Philippines has laws that require people to wear helmets, fasten seat belts, prohibit cell phone use, or get drunk while driving in traffic. There are two functions of traffic law enforcement in the Philippines: To promote citizens’ compliance with traffic laws by enforcing laws and regulations to prevent bad situations from happening. Surely, law enforcement is there to protect the safety of residents when participating in transportation. The following are the findings of the study based on the sub-problems formulated: Sub- problem no. 1 Demographic profile of the respondents in terms of: 1.1 Age, On the part of the Traffic Enforcer, the majority of the respondents are 26 – 33 yrs. Old with a frequency of 14 or 70 percent. On the part of the Brgy. Personnel: the majority of the respondents are 26 – 30 years old, with a frequency of 16 or 80 percent. 1.2 Sex: On the part of the traffic enforcer, the majority of the respondents are male, with a frequency of 20 or 100 percent, on the part of the Brgy. Personnel: the majority of the respondents are male, with a frequency of 17 or 85 percent. 1.3 Civil Status: On the part of the traffic enforcer and barangay respondents, both groups got married with a frequency of 20 or 100 percent.